The Impact of Floods on Food Insecurity and Vulnerability in Democratic Republic of the Congo - Alzaki Alhelo (My University, 2026)
I study the impacts of floods on household food insecurity and vulnerability in Democratic Republic of the Congo. I combine household-level data with two measures of exposure to floods, self-reported exposure and an objective indicator of large flood events at territory-level. I exploit territory-level variation in timing of exposure to floods combined with exposure to floods to identify causal impacts. I find that self-reported exposure to flood is associated with higher food insecurity and greater reliance on negative coping strategies. In contrast, causal estimates based on an objective measure of exposure to floods suggest that exposure to floods does not significantly change consumption frequency or dietary diversity but is associated with improved food security in Eastern DRC. I explore whether this pattern is driven by short-run economic activity or increased agricultural production and find suggestive evidence that exposure to floods in this context expand cultivated land.